Studying the experience of small projects in Syria (2001 – 2017) - Shuraki, Mada; Ali, Rama (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to study reality small business in Syria between 2001 & 2017, through discussing, the different definitions of small business and the criteria for determining them comparison for other countries. It also highlights the reality of these business in Syria over the past sixteen-year. Moreover, it presents the most important challenges that the work of these business faces, in addition, it discusses the most prominent laws concerning the small business. Finally, the research presents a number of recommendations to activate the role of this important sector.